Случаи тератоза и гинандроморфизма у некоторых видов хрущей рода Polyphylla (Coleoptera, Melolonthidae) - Васько, Б.Н. (Вестник зоологии, 2008)
Для четырех видов Polyphylla (s. str.) fullo (Linnaeus, 1758), P. (s. str.) olivieri (Castelnau, 1840), P. (Mesopolyphylla) tridentata Reitter, 1890 и P. (Xerasiobia) adspersa Motschulsky, 1853 приведены: краткое описание отличий от типичного состояния признаков вида, рисунки деталей строения и краткий обзор литературы. Обнаружен 1 экз. гинандроморфа P. fullo, по которому дано описание и приведены иллюстрации. Для хрущей рода Polyphylla случаи аномалий и гинандроморфизма отмечаются впервые. For four species — Polyphylla (s. str.) fullo (Linnaeus, 1758), P. (s. str.) olivieri (Castelnau, 1840), P. (Mesopolyphylla) tridentata Reitter, 1890, and P. (Xerasiobia) adspersa Motschulsky, 1853 the brief descriptions of the detailed declinations from the typical structures of species are given, as well as the figures of the different parts of these structures and a list of the literature references. One specimen of gynandromorphic P. fullo was collected, and its morphological description together with corresponding illustrations is represented. For cockchafers above mentioned anomalies and gynandromorphism are recorded for the first time.